Access to Medical Knowledge: Libraries, Digitization, and the Public Good - Ruth A. Riley (Issues in Science and Technology Librarianship)
This article reviews the book Access to Medical Knowledge: Libraries, Digitization, and the Public Good by Frances K. Groen.